A Case report on efficacy of SPHEDM-S on the treatment of chronic, incurable wounds in Meru County - Gichuki, Charity; Katoloki, James (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
We wish to report a breakthrough treatment of chronic wounds using a new drug combination pseudo-named SPHEDM-S, that has proven to cure otherwise untreatable wounds including diabetic, cancerous, venous and extensive burn wounds. Our observation when using this combination is that chronic wounds become odorless and painless, granulate faster. SPHEDM-S further significantly reduces sepsis, is hemostatic and stimulates epithelialization and skin re-growth. This has the overall effect of reduced hospital stays and lowers the cost of treatment. SPHEDM-S, a combination of five drugs consisting silver sulphadiazine (250g), silver nitrate (5ml of 0.01%w/v), metronidazole (1gm), doxycycline (500mg) and phenytoin (300mg). The trigger for our research was the observation that the use of silver sulphadiazine, metronidazole and phenytoin in combination gave better wound healing outcomes than the application of silver sulphadiazine alone, the recommended burn wound management drug. The triple combination gave better granulation and infection management leading to faster wound healing. We further observed that practicing clinicians were shifting from the use of silver sulphadiazine to silver nitrate solution at 0.01%w/v claiming that wounds dried faster than when silver sulphadiazine was used. Furthermore, the Meditec Group (the manufacturers of silver nitrate spray) indicated that use of silver nitrate was effective against drug resistant strains of wound microbes. We also observed that phenytoin an anticonvulsant, causes gingival hyperplasia as a side effect and desired to investigate if this would enhance wound granulation and re-epithelialization. We therefore added phenytoin to the combination and observed that it not only hastened deep wound healing but also had analgesic effect on painful wounds. This paper reports the initial clinical case reports using SPHEDM-S on deep and hard-healing to non-healing wounds.